DSP architecture design essentials - Marković, Dejan; Brodersen, Robert W. (Electrical Engineering Essentials, 2012)
This book addresses the gap between DSP algorithm design and implementation, using an approach to DSP architecture design that merges algorithm and system specifications with the intrinsic computational capability of the underlying technology.